(untitled) (Italian Journal of Public Health, 2010)
Background: The main purpose of this study was to identify and describe knowledge, beliefs and attitudes towards HIV infection and risky sexual behaviour in female medical freshmen in order to evaluate the possibility of female medical student-based peer education. Methods: Researchers surveyed 560 freshmen: 280 medical students and 280 non medical students at two Italian Universities, collecting the data through anonymous, self-administered questionnaires. Data were codified and statistical analysis was computed using Statistica and Openstat 4 software. Results: Female medical freshmen showed higher levels of knowledge and risk perception about HIV infection, and higher levels of self-awareness in preventing infection when compared with non-medical freshmen. Moreover, medical student’s had a lower rate of sexual activity and a higher rate of condom usage. Conclusions: Our data leads to the hypothesis that the involvement of female medical students in developing and providing safe sex education may be an important and effective way of better enhancing young people’s knowledge, attitude and behaviour towards the prevention of HIV and other sexually transmitted infections